The use of a multinomial logistic regression model in analyzing micro enterprise financing sources in rural areas, Malaysia - Muhammad Ammar Shafi, Muhammad Ammar Shafi; Abdul Razak, Mohd Farhan; Zulkipli, Hafizah; Ismail, Shuhaida; Ahmad, Nurazwa; Muhamad Nasir, Muhamad Nasyat; Zakaria, Aliya Syaffa (2024)
An effective source of financing plays a role among micro enterprises because it can help micro-enterprises survive, function, and grow in their business. This shows that the type of financing resources needed to drive the productivity growth of micro-enterprises to build and promote the rural financial system is needed to drive the overall growth of the economy in Malaysia. Microenterprises suffer from a lack of resources because small firms and involved in the start-up stage, and lenders are not interested in providing financing for this group. The problem of this study is that access to financing sources is one of the main obstacles to the development of micro-enterprises to build a successful business. The main objective of this study is to examine the probability between financing problems and entrepreneurial skills that have the highest influence on funding sources. The study respondents consisted of managers of micro-enterprises who do business in the Batu Pahat District area. The research conducted is quantitative by using questionnaire instruments for the purpose of data collection. A total of 118 people were made as respondents and the data obtained will be analyzed using the Statistical Package for Social Science (SPSS) version 23.0 software. The collected data were analyzed using descriptive analysis, correlation analysis, and binary logistic regression. The results of the study found that financing problems and entrepreneurial skills affect funding sources with a moderate degree of tendency. In addition, the results of this study also found that the probability ratio of micro-enterprises with entrepreneurial skills will have a better advantage in influencing effective funding sources.